CD40 ligand‐expressing recombinant vaccinia virus promotes the generation of CD8+ central memory T cells. Issue 2 (2nd December 2015) - Trella, Emanuele; Raafat, Nermin; Mengus, Chantal; Traunecker, Emmanuel; Governa, Valeria; Heidtmann, Swantje; Heberer, Michael; Oertli, Daniel; Spagnoli, Giulio C.; Zajac, Paul
Abstract : Central memory CD8 + T cells (TCM ) play key roles in the protective immunity against infectious agents, cancer immunotherapy, and adoptive treatments of malignant and viral diseases. CD8 + TCM cells are characterized by specific phenotypes, homing, and proliferative capacities. However, CD8 + TCM ‐cell generation is challenging, and usually requires CD4 + CD40L + T‐cell "help" during the priming of naïve CD8 + T cells. We have generated a replication incompetent CD40 ligand‐expressing recombinant vaccinia virus (rVV40L) to promote the differentiation of human naïve CD8 + T cells into TCM specific for viral and tumor‐associated antigens. Soluble CD40 ligand recombinant protein (sCD40L), and vaccinia virus wild‐type (VV WT), alone or in combination, were used as controls. Here, we show that, in the absence of CD4 + T cells, a single "in vitro" stimulation of naïve CD8 + T cells by rVV40L‐infected nonprofessional CD14 + antigen presenting cells promotes the rapid generation of viral or tumor associated antigen‐specific CD8 + T cells displaying TCM phenotypic and functional properties. These observations demonstrate the high ability of rVV40L to fine tune CD8 + mediated immune responses, and strongly support the use of similar reagents for clinical immunization and adoptive immunotherapy purposes.